2017
DOI: 10.1002/jum.14362
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Body Mass Index and Amniotic Fluid Index in Late Gestation

Abstract: The maternal BMI is not associated with oligohydramnios in late gestation. An increasing maternal BMI significantly increases the risk of primary cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies on the impact of obesity on the accuracy and reproducibility of sonographic assessments have shown mixed results 14–16 . Ultimately, Blitz et al demonstrated no significant difference in the diagnosis of oligohydramnios with increasing BMI 13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on the impact of obesity on the accuracy and reproducibility of sonographic assessments have shown mixed results 14–16 . Ultimately, Blitz et al demonstrated no significant difference in the diagnosis of oligohydramnios with increasing BMI 13 …”
Section: Discussionmentioning
confidence: 99%
“…5,7,12 A recent study by Blitz et al approached this question from a different angle and asked whether the technical challenges of scanning obese patients negatively impacted assessment of amniotic fluid. 13 In this context, abnormalities of amniotic fluid-specifically, oligohydramnios-would reflect technical limitations rather than an underlying pathophysiological process. Previous studies on the impact of obesity on the accuracy and reproducibility of sonographic assessments have shown mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations